A Comprehensive Systematic Review of The Association between High-Protein Diet and Body Composition in Obese Patients - Mohamad Fadli; Hendandy Driya Pamungkas (International Medical Journal Corp. Ltd, 2026)
Introduction: Obesity is a global health concern associated with adverse metabolic outcomes. High-protein diets (HPD) are increasingly utilized for weight management, but their specific effects on body composition in obese populations require comprehensive evaluation. This systematic review aims to synthesize evidence from randomized controlled trials examining the association between HPD and body composition changes in obese adults. Methods: A systematic review of randomized controlled trials, etc published up to 2024 was conducted. Studies included obese adults (BMI ≥30 kg/m²) comparing HPD (≥1.2 g/kg body weight/day or >20% total energy from protein) with standard-protein diets. Primary outcomes included changes in total body weight, fat mass, lean body mass, and regional adiposity. Data were extracted on protein intervention details, comparison groups, population characteristics, and outcome measurements. Results: Eighty studies comprising over 4,300 participants were included. HPD produced significantly greater weight loss (additional 0.67 kg; 95% CI: -0.23, -0.03) and fat mass reduction (additional 0.57 kg; 95% CI: -0.24, -0.04) compared to standard-protein diets (1,64). Lean mass preservation favored HPD (0.43 kg; 95% CI: 0.09-0.78) (2). Visceral and trunk fat reductions were consistently greater with HPD, particularly in individuals with elevated triglycerides (5,8). Protein intake exceeding 1.3 g/kg/day was associated with muscle mass preservation, while intakes below 1.0 g/kg/day increased muscle loss risk (9). Combining HPD with resistance exercise produced superior outcomes (6,7). Sex-specific responses were observed, with men losing more trunk fat and women more subcutaneous fat (20,27). Genetic variants (FTO, TFAP2B) modulated individual responses (3,73). Discussion: HPD confer modest but clinically meaningful benefits for body composition during energy restriction, primarily through enhanced fat loss and preferential visceral adipose tissue reduction. Lean mass preservation depends on achieving adequate protein thresholds (>1.3 g/kg/day), even protein distribution across meals (≥30 g/meal), and concurrent resistance exercise. Metabolic status, age, and genetic factors influence individual responses. Long-term adherence remains challenging, with protein intakes converging between groups over 12-24 months. Conclusion: High-protein diets (1.2-1.6 g/kg/day or 25-35% total energy) are effective for improving body composition in obese adults, particularly when combined with resistance exercise and structured meal plans. Future research should focus on personalized approaches based on genetic and metabolic phenotypes.